Conventional stimulation protocol failed to produce mature oocytes : rescue ivm resulted in six pregnancies after invitro fertilization and embryo transfer - Gunasheela, Sulochana; Gunasheela, Devika; Gupta, Santosh; Peter, Joshua (Journal of Experimental Sciences, 2011)
When conventional stimulation protocol in IVF cycle fails to produce mature oocytes, many a times, the cycle is cancelled and the patient is disappointed.Ã‚Â Now that in-vitro maturation of oocyte is possible in view of commercial availability of media, perhaps it may be mandatory to retrieve immature oocytes and mature them in-vitro, freeze them if necessary and fertilize, develop embryos for transfer in order to help couples to achieve pregnancy.Ã‚Â Thus maturation in-vitro of GVs has become an important adjuvant for treating PCOS and in particular poor responders to gonadotrophin stimulation.Ã‚Â Our study is interesting because in spite of conventional stimulation protocol, we failed to recover any mature oocytes in eleven women when the average follicles size being 17mm at the time of hCG.Ã‚Â However, maturing these oocytes in-vitro, as a rescue measure, resulted in 50% of these women becoming pregnant after embryo transfer.